2022
DOI: 10.7717/peerj.13021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of magnification factor by Galilean loupes on working posture of dental students in simulated clinical procedures: associations between direct and observational measurements

Abstract: Objectives To determine the effect of different levels of Galilean loupe magnification on working posture as measured by compliance with ergonomic posture positions, angular deviation from the neutral position of the neck, and muscle activation in the neck and upper back region during simulated clinical conditions. Methods An experimental laboratory study was performed in which the dependent variables were compliance with ergonomic posture requirements while performing simulated restorative procedures in Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…One of the strategies that have been suggested for the prevention of these disorders is using magnification at the operative field. [6][7][8][9][10]12,13,15,16,26,27 Although the results obtained in this study do not show a significant contribution of magnification loupes to visual acuity, previous studies have proven their benefits on working posture, 9,15 indicating that these devices can be effective in helping future dentists adopt ergonomic postures and maintain their occupational health.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations
“…One of the strategies that have been suggested for the prevention of these disorders is using magnification at the operative field. [6][7][8][9][10]12,13,15,16,26,27 Although the results obtained in this study do not show a significant contribution of magnification loupes to visual acuity, previous studies have proven their benefits on working posture, 9,15 indicating that these devices can be effective in helping future dentists adopt ergonomic postures and maintain their occupational health.…”
Section: Discussionmentioning
confidence: 74%
“…This reinforces the importance of implementing a training program for the use of magnified loupes prior to clinical care. 9,15 In addition to verifying the influence of magnification loupes on visual acuity, we assessed their effect on the distance between the eyes of the operator and mouth of the dental phantom head. We observed that both the naked eye and the different magnification levels of the evaluated loupes presented a working distance superior to that of the simulator while similar to each other.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pazos et al (2020) [19] found that using both the Galilean and Keplerian magnification systems improved the working posture during the performance of simulated clinical procedures. Thereby, the implementation of magnification loupes for better visualization of the operative field may be positive to help the students in maintaining the distance of 30 to 40cm between the patient´s mouth and the operator´s eyes and, consequently, improve the adoption of ergonomic posture [20,21].…”
Section: Discussionmentioning
confidence: 99%